Metafora Konseptual Pada Lirik Lagu Soundtrack Anime "Fullmetal Alchemist: Brotherhood": Kajian Semantik Kognitif - -, Muhammad Fauzan; Aibonotika, Arza; Rahayu, Nana (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2023)
This study discusses about the song lyrics that containt conceptual metaphore from soundtrack of animation called “Fullmetal Alchemist: Brotherhood”. Every singer has a variety of language style of their song lyrics to make it more interesting to hear, like metaphore. In this study, we will discuss about the song lyrics that containt conceptual metaphore from soundtrack of animation called “Fullmetal Alchemist: Brotherhood”. The data from this study is the song lyrics from anime soundtrack “Fullmetal Alchemist: Brotherhood” that contain conceptual metaphore. The method used in this study is a qualitative descriptive method. The source of data from this research is 10 types of songs from soundtrack of animation called “Fullmetal Alchemist: Brotherhood”. There is 4 types of conceptual metaphore found in anime soundtrack of “Fullmetal Alchemist: Brotherhood”, its structural metaphore, orientational metaphore, ontological metahpore and personification ontologikal metaphore. The results of the analysis of conceptual metahpore that reveal a few types of meaning, like leksical meaning, and conceptual meaning. Every conceptual metaphor also have their source domain as a metaphore expression, and target domain as a meaning. Each conceptual metaphore are founded also contain a few types of image schemas, which is force schema, existence schema, space schema, and containtment schema.